จุดกำเนิดและพัฒนาการของรูปแบบและเนื้อหานิตยสารดาราภาพยนตร์และทีวีพูล - แทนใจ โพธิแท่น (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
This research is a combination of in-depth interview and content analysis with the aim to study the development of form and content presentation of both magazines. The findings of the research are as follows. Darapapyoun magazine was first published in 1977 by Tanoo Chonglertjanya. He is motivated by the desire to publish an entertainment magazine, the main policy being to give information about motion picture business as well as useful information about health. T.V. Pool magazine, on the other hand, was published much later in 1990 by Kriengsak Sakulchai. His aim is to publish an entertainment magazine that can deliberately convey the most expressive opinions to his readers. The main policy of T.V. Pool is to present information about television network with an emphasis on actual news in depth. The development of Darapapyoun magazine can be grouped into 3 stages. The first stage (1977-1984) mainly placed an emphasis on the presentation of information about the celluloid world. The second stage (1985-1997) added information about television together with motion pictures, highlighting on political content in the hard news scoop. The third stage (1998-2002) saw an increase in television content and a change in the look of the magazine to emphasize fashion in order to keep up with the trend. The development of T.V. Pool magazine can be grouped into 2 stages. The first stage (1990-1994) put an emphasis on sensational news and lively reviews using harsh language to increase circulation. The second stage (1995-2001) saw an adjustment in terms of content towards a less sensational tone while adding information about the lifestyle of stars and show business. The factors leading to the success of both magazines are 1) the adjustment in form and content to suit the taste of the readers, 2) the strategy in designing the content that is not only outstanding but also unique of each individual magazine, 3) the strategy in creating the magazineʼs images to attract the readers, and finally 4) the use of different marketing strategies, such as pricing, sales promotion, advertising and establishing relationship with other media.